Black larder beetle, incinerator beetle, Dermestes ater DeGeer (Insecta: Coleoptera: Dermestidae) - Nurmastini S. Bujang; Phillip E. Kaufman (EDIS)
EENY480, a 6-page illustrated fact sheet by Nurmastini S. Bujang and Phillip E. Kaufman, is part of the Featured Creatures collection. It describes this cosmopolitan species that feeds on various plant and animal products, as well as dead insects and carrion — synonymy, distribution, description, life cycle, economic importance, veterinary importance, forensic importance, and management. Includes references. Published by the UF Department of Entomology and Nematology, August 2010.